2000
DOI: 10.1128/jvi.74.12.5477-5485.2000
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Chimeric Yellow Fever-Dengue Type 2 Virus Is Immunogenic and Protective in Nonhuman Primates

Abstract: A chimeric yellow fever (YF)-dengue type 2 (dengue-2) virus (ChimeriVax-D2) was constructed using a recombinant cDNA infectious clone of a YF vaccine strain (YF 17D) as a backbone into which we inserted the premembrane (prM) and envelope (E) genes of dengue-2 virus (strain PUO-218 from a case of dengue fever in Bangkok, Thailand). The chimeric virus was recovered from the supernatant of Vero cells transfected with RNA transcripts and amplified once in these cells to yield a titer of 6.3 log 10 PFU/ml. The Chim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
140
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(151 citation statements)
references
References 29 publications
(49 reference statements)
8
140
1
2
Order By: Relevance
“…1b). These findings are consistent with the previous observations that chimeric flaviviruses could express the prM and E genes of heterologous flaviviruses, and exhibited growth-similar characteristics (Arroyo et al, 2001;Bhatt et al, 2000;Chambers et al, 1999;Guirakhoo et al, 2000;Pletnev et al, 2001Pletnev et al, , 2003.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…1b). These findings are consistent with the previous observations that chimeric flaviviruses could express the prM and E genes of heterologous flaviviruses, and exhibited growth-similar characteristics (Arroyo et al, 2001;Bhatt et al, 2000;Chambers et al, 1999;Guirakhoo et al, 2000;Pletnev et al, 2001Pletnev et al, , 2003.…”
supporting
confidence: 82%
“…Especially, using live attenuated strains as the genetic backbone, multiple versions of chimeric flaviviruses have been successfully designed and well-explored in the development of vaccines against DENV, WNV, JEV and TBEV (Brandler et al, 2005;Chambers et al, 1999;Guirakhoo et al, 2000;Guy & Jackson, 2016;Pletnev et al, 2002;Wright et al, 2008). The JEV live attenuated vaccine virus SA14-14-2 has been widely used in most JEV-endemic countries (Yu, 2010) with an excellent safety and efficacy profile (Bista et al, 2001;Kumar et al, 2009;Tandan et al, 2007).…”
mentioning
confidence: 99%
“…Since the first reports of the generation of intratypic (DEN2/DEN4) and intertypic (TBE/ DEN4) antigenic chimeric flaviviruses using reverse genetics [15,22], numerous chimeric viruses have been created using genes from tick-borne and mosquito-borne flaviviruses, and many of these viruses are currently being evaluated as vaccines [10,16,19,20,[23][24][25][26]. Recent clinical studies have indicated that antigenic chimeric flaviviruses are attenuated and immunogenic in human volunteers and may serve as live attenuated virus vaccines for protection against disease caused by DEN, JE, WN, and TBE viruses [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…3A). In this experiment, the effect of WN preimmunity was less pronounced compared with the effect of YF preimmunity on ChimeriVax-DEN2 vaccine in a NHP study described previously (26).…”
mentioning
confidence: 91%